Konsep Dasar Dan Landasan Hukum Pasar Modal Syariah Di Indonesia : Tinjauan Regulasi Dan Prinsip Syariah - Alda Andrini; Asyhari Abdillah Siregar; Fahriza Alyanisa; Gilang Saka Maulana; nabilahirwani; Sandi Sipahutar; Maryam Batubara (Nirta Learning Centre, 2025)
The Islamic capital market is an integral part of the Islamic financial system in Indonesia, based on Islamic principles such as justice, transparency, and the prohibition of usury (riba). This study aims to explain the fundamental concepts and examine the legal foundations of the Islamic capital market in Indonesia by reviewing existing regulations and their compliance with sharia principles. The method used is a literature review of OJK (Financial Services Authority) regulations, DSN-MUI (National Sharia Council – Indonesian Ulema Council) fatwas, and academic sources related to the Islamic capital market. The findings indicate that the Islamic capital market in Indonesia has a solid legal foundation both from the national legal framework and Islamic fatwas. Pasar modal syariah merupakan bagian integral dari sistem keuangan syariah di Indonesia yang berlandaskan pada prinsip-prinsip Islam, seperti keadilan, transparansi, dan larangan riba. Penelitian ini bertujuan untuk menguraikan konsep dasar serta menelaah landasan hukum pasar modal syariah di Indonesia dengan meninjau regulasi yang berlaku dan kesesuaiannya dengan prinsip-prinsip syariah. Metode yang digunakan adalah studi literatur terhadap regulasi OJK, Fatwa DSN-MUI, serta literatur akademik terkait pasar modal syariah. Hasil kajian menunjukkan bahwa pasar modal syariah di Indonesia memiliki dasar hukum yang cukup kuat, baik dari sisi perundang-undangan nasional maupun fatwa syariah